Validating the factors influencing social commerce adoption in small and medium enterprise in Malaysia - Walid Abdullah Ali; Muriati Mukhtar; Ibrahim Mohamed (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Electronic commerce has been growing at a rapid rate in many countries, including developing countries. In recent years, social media and social networking sites have become popular and such popularity has led to a novel e-commerce branch known as social commerce. In Malaysia, it is observed that individuals and organizations have begun to sell and purchase using social media. But studies on s-commerce adoption in Malaysia are still lacking. Therefore, this study aimed to investigate the effects of technological, organizational, and trust factors on social commerce adoption among SMEs in Malaysia. This paper presented the factors, collected from literature, which influence the adoption of social commerce, and the results of an exploratory pilot study.